2014
DOI: 10.1016/j.taap.2014.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of binding affinity and efficacy of thyroid hormone receptor ligands using QSAR and structure-based modeling methods

Abstract: The thyroid hormone receptor (THR) is an important member of the nuclear receptor family that can be activated by endocrine disrupting chemicals (EDC). Quantitative Structure-Activity Relationship (QSAR) models have been developed to facilitate the prioritization of THR-mediated EDC for the experimental validation. The largest database of binding affinities available at the time of the study for ligand binding domain (LBD) of THRβ was assembled to generate both continuous and classification QSAR models with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 56 publications
(115 reference statements)
0
26
0
Order By: Relevance
“…Chang et al (2015) at NICEATM conducted an in vitro-to-in vivo extrapolation (IVIVE) study of 230 potentially ER-active environmental chemicals tested in Tox21 10K screening, suggesting the need of compound pharmacokinetics in prioritising chemicals for further endocrine-related tests. Additionally, Politi et al (2014) demonstrated the usefulness of HTS data in confirming results generated from virtual screening for TR ligands. To supplement current toxicity assessment methods with computational modelling, NCATS launched a crowdsource challenge in 2014 that asked the participants to build computational models predictive of chemical toxicity .…”
Section: Predictive Modellingmentioning
confidence: 71%
“…Chang et al (2015) at NICEATM conducted an in vitro-to-in vivo extrapolation (IVIVE) study of 230 potentially ER-active environmental chemicals tested in Tox21 10K screening, suggesting the need of compound pharmacokinetics in prioritising chemicals for further endocrine-related tests. Additionally, Politi et al (2014) demonstrated the usefulness of HTS data in confirming results generated from virtual screening for TR ligands. To supplement current toxicity assessment methods with computational modelling, NCATS launched a crowdsource challenge in 2014 that asked the participants to build computational models predictive of chemical toxicity .…”
Section: Predictive Modellingmentioning
confidence: 71%
“…The chemical structures for 181 compounds able to bind at AF-2 domains taken in the literature: collected IC50 values falls into range from 0.310 mM to 100 mM for AF-2 domains [1]. The endpoint under consideration is the negative decimal logarithm of half maximal inhibitory concentration (pIC50) [1].…”
Section: Datamentioning
confidence: 99%
“…The endpoint under consideration is the negative decimal logarithm of half maximal inhibitory concentration (pIC50) [1]. The available data were three times randomly split into the training (z75%), calibration (z12.5%), and validation (z12.5%) sets.…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations